Purification of wastewater by Algae (Journal of the College of Basic Education, 2023)
The two micro algae chlorella & Scenedesmus were used inpurification of wastewater with investment of sludge bacteria existing inthe same water. The two algae were isolated from Tigris river startly them grown inmedium prepared in the lab independent on the water of the river as abasic medium in order to use these growths as algal inoculums in the laterexperiments. These algae were tried to grow on the samples of wastewater inBaghdad to produce a biomass utilized as a source of food and feed. Labexperiments were achieved to study the effect of temperature, conc. ofsalt and shaking period on the extraction of protein taken from the massof algal growth.